Evaluating Financing Costs for Multinational Subsidiaries - Shapiro, Alan C. (Journal of International Business Studies, 1975)
This paper presents a methodology for determining the true costs of alternative sources of financing for the multinational corporation when the risk of exchange rate changes is present and different tax rates and regulations are in effect. The cost formulas presented can then be used to calculate the cheapest financing source given the expected exchange rate changes.